Surface structure and electronic properties of Pt-Fe/C nanocatalysts and their relation with catalytic activity for oxygen reduction - Malheiro, A. R. [UNESP]; Perez, J. [UNESP]; Villullas, Hebe de Las Mercedes [UNESP] (Elsevier B.V., 2010)
In this work, physical and catalytic properties of Pt-Fe/C nanocatalysts of nominal compositions Pt;Fe 70:30 and 50:50, prepared by a polyol process using a long-chain diol as reducer (hexadecanediol) and oleic acid and oleylamine as stabilizers, are reported. As-prepared materials have very small particle size (2.2 nm), narrow particle size distribution, and homogeneous dispersion on the carbon support. The average compositions determined by energy dispersive X-ray analysis are Pt(75)Fe(25)/C and Pt(60)Fe(40)/C. Data for samples submitted to heat treatment in hydrogen atmosphere to induce Pt surface segregation are also presented. X-ray diffraction and transmission electronic microscopy are used to examine all as-prepared and heat-treated catalysts. Electronic properties are analyzed based on in situ dispersive X-ray absorption spectroscopy data. Measurements of electrocatalytic activity for oxygen reduction show that all Pt-Fe/C have electrocatalytic activities superior to that of Pt/C. Nanocatalysts with a Pt-rich surface have an enhanced performance for the reduction of oxygen but measurements carried out in methanol containing solutions show that Pt-enriched surfaces have an inferior methanol tolerance. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electrocatalyst; Oxygen reduction reaction; Nanostructured materials; Pt-based nanoparticles